TRANSFORMATION OF PUBLIC SERVICES IN THE IMPLEMENTATION OF GOVERNMENT ADMINISTRATION - Loso Judijanto; Muhammad Abdul Kahar; Asni Hasanuddin (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2026)
Public service transformation is a crucial strategic step in implementing more responsive and accountable government administration. For long- term success, this transformation must be supported by strong leadership, effective change management, and strategies that focus on sustainability and inclusiveness. This study explores the transformation of public services in the implementation of government administration, focusing on the impacts on efficiency, transparency, accountability, and public participation. This transformation, which is mainly driven by digitalization and technological innovation, is expected to improve the quality of public services and strengthen good governance. This transformation contributes significantly to improving operational efficiency, reducing bureaucracy, and accelerating the service process. In addition, transparency and accountability in government are strengthened through easier access to public information and a more effective performance monitoring system. However, this study also identifies challenges faced, including the digital divide that can widen the inequality in access to public services. Therefore, efforts are needed to bridge this gap and ensure inclusiveness in public service transformation.